Indonesian Maritime Diplomacy: Realizing the Global Maritime Fulcrum Through IORA - Amri, Ulil; Zahidi, M Syaprin (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2023)
This article discusses why the Indian Ocean Rim Association (IORA) is significant for Indonesia and how Indonesia plays a strategic role in IORA to realize national interests and advance its vision as the World Maritime Axis? In answering these questions, we build arguments based on Christian Le Miere's theory of maritime diplomacy and Helen Milner's theory of international cooperation. The argument in this article consists of two things. First, IORA is very significant for Indonesia because the organization has a common vision with Indonesia's national interest. Second, in order to achieve this goal, the Indonesian government utilizes cooperative and persuasive maritime diplomacy as a means of enhancing international cooperation. This is demonstrated by Indonesia's involvement in encouraging negotiations and facilitating cooperation in the IORA forum. This is also reinforced by Indonesia's election as chair of IORA for the period 2015 to 2017 as a manifestation of Indonesia's existence as a maritime country in the international arena.